Electrochemical Aspects of Mass Spectrometry: Atmospheric Pressure Ionization and Ambient Ionization for Bioanalysis. Issue 4 (27th January 2017) - Yuill, Elizabeth M.; Baker, Lane A.
Abstract: This MiniReview details the evolution and present state of combined electrochemical (EC) and atmospheric pressure sampling/ionization mass spectrometric (MS) techniques, with an emphasis on biologically relevant investigations. Particular attention is paid to how innate EC processes can be exploited to gain additional information about an analyte, and how these effects influence experimental design. A general overview of EC‐MS techniques underscores the complementary nature of the two techniques. Abstract : Complementary combination : When electrochemical (EC) and mass spectrometric (MS) fields intersect, additional information is gained. A survey of atmospheric pressure ionization and ambient ionization techniques demonstrates the complementary and synergetic nature of EC and MS. EC‐MS hybridization is particularly useful for biological investigations, where targeted analysis and reaction monitoring reveal details that could not be learned from EC or MS separately.